Interannual and Seasonal Variation of Optical and Microphysical Properties of Aerosol in the Baikal Region - Ayuna Dementeva; Galina Zhamsueva; Alexander Zayakhanov; Vadim Tcydypov (Atmosphere, 2022)
The paper analyzes the interannual, seasonal variations of the optical and microphysical characteristics of aerosol in the Baikal region atmosphere according to measurements using the CIMEL sun photometer of the AERONET network at Tory station and according to the data of expedition measurements using the SP-9 sun photometer on the southeastern coast of Lake Baikal from 2010 to 2020. It is shown that in recent years, there has been an increase of the average monthly aerosol optical depth (AOD) values in the summer months, which is consistent with an increase in smoke emission due to annual large-scale wildfires in the boreal forests of Siberia and Yakutia in summer. Aerosol classification was carried out based on filtration and selection of the prevailing types of aerosols by analysis of aerosol optical depth and Angstrom exponent. It was revealed that in summer, the proportion of the smoke component of the aerosol optical depth increases to 30% compared to the spring. In the presence of smoke advection, the close relationship of AOD with the concentrations of the microdispersed aerosol fraction PM10 and PM2.5 was revealed. The correlation coefficients between the concentration of particulate matter (PM10 and PM2.5) and AOD were 0.87 and 0.86, respectively.